The adaptation behaviour of marine fishermen towards climate change and food security: An application of the theory of planned behaviour and health belief model - Begum, Mahfuza (MDPI, 2022)
Key food production sectors, such as fisheries, are predicted to be severely impacted by climate change, which threatens food security. Owing to the direct influence of climate change on the lives and means of livelihood of marine fishing communities, effective adaptation methods are required to ensure the well-being of coastal communities. Thus, the goal of this study is to examine the various factors that impact the adaptation behaviour of marine fishermen towards climate change. To this end, data were collected from 312 Bangladeshi fishermen using survey questionnaires and subsequently analysed by employing partial least square structural equation modelling (PLS-SEM). Our findings reveal a significant and positive association between all components (perceived severity, perceived benefit and perceived barrier) of the Health Belief Model (HBM) and marine fishermen's adaptation behaviour. However, the perceived susceptibility component of the HBM had no effect on the climate change adaption behaviour of marine fishermen. Likewise, the findings indicate that awareness influences attitude, which in turn impacts the adaption behaviour of marine fishermen. Furthermore, the study results establish the indirect mediating role of awareness and attitude with respect to the adaptation behaviour of marine fishers. The findings of this study can be adopted by policymakers to develop adaptation strategies to aid marine fishermen in adapting to climatic effects. Furthermore, the various responses of marine fishermen to climate change will also serve as a useful source of information for the government. In summary, the information generated from this research can serve as a practical basis to foster adaptation behaviour among marine fishers and advance adaptation policies at the national level, not only in Bangladesh but also for other coastal communities that are at risk as a result of climate change.